Accountability Determinant Model Through Collaboration in Local Government in South Sumatera (International Forum of Researchers and Lecturers, 2025)
Accountability is a fundamental principle of good governance, particularly at the local government level, which spearheads public service delivery. However, the implementation of accountability at the regional level still faces various structural and cultural challenges. South Sumatra Province offers an interesting example, where the Government Agency Performance Accountability (SAKIP) and the Regional Financial Management Index (IPKD) have consistently shown suboptimal performance in recent years. This phenomenon raises critical questions about the factors influencing accountability and how the interaction between these variables can shape a model for strengthening regional governance. This study aims to analyze the influence of integrity, internal control, leadership, and participation on accountability, considering collaboration as a mediating variable. Collaboration is viewed as a strategic mechanism for strengthening coordination, efficiency, and transparency between government organizations. The research method used is a quantitative approach with Structural Equation Modeling – Partial Least Squares (SEM-PLS) analysis of primary data collected from respondents within the local government in South Sumatra. The results indicate that integrity, internal control, leadership, and community participation significantly influence collaboration. Furthermore, collaboration has been shown to significantly contribute to increased accountability. Furthermore, collaboration is also a significant mediator in the relationship between independent variables and accountability. Thus, these findings emphasize the importance of building a collaborative work ecosystem as a prerequisite for successful regional bureaucratic reform. This research provides practical implications for regional governments in designing financial management and public service policies based on synergy, integrity, and multi-stakeholder involvement to sustainably enhance accountability.